Prehypertension prior to pregnancy is associated with hypertensive disorders of pregnancy and postpartum metabolic syndrome in Chinese women - Shu-Cheng Ye; Ning Yang; Mao-Ti Wei; Xin Zhang; Shou-Ling Wu; Yu-Ming LI (Taylor & Francis Group, 2020)
Objective To examined whether prehypertension prior to pregnancy increased the risk of hypertensive disorders of pregnancy (HDP) and postpartum metabolic syndrome. Methods 1060 singleton pregnancy women with physical examination data before pregnancy were enrolled through the Kailuan study. Women with pre-pregnancy hypertension, metabolic syndrome, or no postpartum follow-up data were excluded. Pre-pregnancy prehypertension was defined as elevated blood pressure (130-139/85-89 mmHg) at the last physical examination before pregnancy. Multivariable Logistic and Cox Regression were used to examine the association between pre-pregnancy prehypertension and outcomes. Kaplan-Meier survival curve was used to analyze the cumulative incidence of postpartum metabolic syndrome. Results Among the 801 women enrolled at baseline, 173 (21.6%) had prehypertension. Overall, 61 women (7.6%) developed HDP. Kaplan-Meier survival curve showed that the incidence of postpartum metabolic syndrome was significantly higher in prehypertensive women. After adjusting for confounders, women with pre-pregnancy prehypertension were 2.09 (95% CI 1.19-3.70) and 1.91 (95% CI 1.23-2.97) times as likely to develop HDP and postpartum metabolic syndrome, compared to normotensive women. Conclusion Women with pre-pregnancy prehypertension may benefit from the more intensive monitor for HDP and postpartum metabolic syndrome.